Comparison of two etanercept regimens for treatment of psoriasis and psoriatic arthritis: PRESTA randomised double blind multicentre trial. (2nd February 2010) - Sterry, Wolfram; Ortonne, Jean-Paul; Kirkham, Bruce; Brocq, Olivier; Robertson, Deborah; Pedersen, Ronald D; Estojak, Joanne; Molta, Charles T; Freundlich, Bruce
Abstract : Objectives To compare the efficacy over 12 weeks of two different etanercept regimens in treating the skin manifestations of psoriasis in patients who also have psoriatic arthritis and to evaluate efficacy and safety over an additional 12 weeks of open label etanercept treatment. Design Randomised double blind multicentre outpatient study. Setting 98 outpatient facilities in Europe, Latin America, and the Asia Pacific region. Participants 752 patients with both psoriasis (evaluated by dermatologists) and psoriatic arthritis (evaluated by rheumatologists). Interventions During the blinded portion of the study, participants were randomised to receive etanercept 50 mg twice weekly (n=379) or 50 mg once weekly (n=373) for 12 weeks by subcutaneous injection. All participants then received open label etanercept 50 mg once weekly for 12 additional weeks, while remaining blinded to the regimen. Main outcome measures The primary efficacy end point was the proportion of participants achieving "clear" or "almost clear" on the physician's global assessment of psoriasis at week 12. Secondary efficacy analyses included psoriasis area and severity index, American College of Rheumatology responses, psoriatic arthritis response criteria, and improvement in joint and tendon disease manifestations. Results At week 12, 46% (176/379) of participants receiving etanercept 50 mg twice weekly achieved a physician's global assessment of psoriasis of "clear" or "almost clear" compared with 32% (119/373) in the group treated with 50 mg once weekly (P<0.001). In contrast, an equally high percentage of participants in both groups achieved psoriatic arthritis response criteria (77% (284/371) in the twice weekly/once weekly group versus 76% (282/371) in the once weekly/once weekly group). Participants treated with 50 mg twice weekly/once weekly had greater mean reductions from baseline in the psoriasis area and severity index at week 12 compared with those who received 50 mg once weekly/once weekly (71% v 62%, P<0.001), with less difference at week 24 (78% v 74%, P<0.110). Joint and tendon disease manifestations improved from baseline in both groups to a similar extent. No new safety signals were seen in either etanercept treatment group, and no significant difference in the safety profiles was observed. Conclusions In participants with active psoriasis and psoriatic arthritis, initial treatment of the psoriasis with etanercept 50 mg twice weekly may allow for more rapid clearance of skin lesions than with 50 mg once weekly. A regimen of 50 mg once weekly seems to be appropriate for treatment of joint and tendon rheumatic symptoms. The choice of regimen should be determined by the clinical needs of the individual patient. Trial registration Clinical trials NCT00245960 .